Online by Choice: Design Options for Flexible K-12 Learning. (2023) - Dolighan, Tim (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2024)
Online by Choice: Design Options for Flexible K-12 Learning by Stephanie Moore and Michael Barbour offers a comprehensive exploration of building a resilient educational ecosystem through blended and online learning options. This review highlights the authors' adept construction of practical, research-based strategies for K-12 communities. By distinguishing between emergency remote learning and purposefully designed online education, Moore and Barbour guide educators in identifying and addressing diverse learner needs in the context of designing and implementing online and blended learning. The authors stress the collaborative effort required between system administrators and teachers for successful online implementation. This review explores the book's utility for educators seeking to enhance their online teaching skills and suggests avenues for future professional learning development in online contexts. Ultimately, Online by Choice emerges as a vital resource for designing effective online learning experiences tailored to the evolving needs of K-12 learners.